2011
DOI: 10.4314/ijbcs.v4i5.65524
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of diamondback moth to insecticides in selected cabbage farms in southern Ghana

Abstract: Resistance of diamondback moth (DBM), Plutella xylostella (L.) to insecticides applied for its control on cabbage was evaluated. DBM populations were tested for susceptibility to three pyrethroids (delatamethrin, lambdacyhalothrin, cypermethrin) and an organophosphate (chlorpyrifos-methyl) insecticide using larvae immersion dose-response technique. Non-specific carboxylesterase activity was used as a measure of DBM resistance. Partial characterization of carboxylesterase by zymogram studies was also undertaken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Bacillus thuringiensis and chlorpyrifos showed higher LC 50 and LC 95 values than those recommended by the manufacturer, as well as increased alpha and beta esterase activity. The high the alpha and beta esterase activity observed in H. armigera population indicates a higher metabolic rate, which may mean some level of resistance, a likely consequence of a long period of exposure to organophosphate, pyrethroids and cry toxin, for example (ODHIAMBO et al, 2010;DAWKAR et al, 2016). These enzymes are able to metabolize the insecticides, due to the high expression of the genes that codify them.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus thuringiensis and chlorpyrifos showed higher LC 50 and LC 95 values than those recommended by the manufacturer, as well as increased alpha and beta esterase activity. The high the alpha and beta esterase activity observed in H. armigera population indicates a higher metabolic rate, which may mean some level of resistance, a likely consequence of a long period of exposure to organophosphate, pyrethroids and cry toxin, for example (ODHIAMBO et al, 2010;DAWKAR et al, 2016). These enzymes are able to metabolize the insecticides, due to the high expression of the genes that codify them.…”
Section: Discussionmentioning
confidence: 99%
“…In urban and peri-urban vegetable cultivation areas around Cotonou, cabbage producers apply insecticides, especially pyrethroids and organophosphates, every 3 to 4 days within a 3-month period before harvesting (James et al, 2010), thereby inducing a high selection pressure. The low susceptibility of field populations of P. xylostella with regard to chemical insecticides was observed in Ghana (West Africa) where Odhiambo et al (2010) showed high LC 50 of 386-802 mg/l and 74,617-170,573 mg/l for deltamethrin and chlorpyrifos ethyl, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As reported from several tropical countries (Talekar and Shelton, 1993;Baek et al, 2005;Nyambo and Löhr, 2005;Ayalew, 2006;Odhiambo et al, 2010;Santos et al, 2011;Zhou et al, 2011;Legwaila et al, 2014), P. xylostella populations from Togo and Benin also appear to be resistant to a number of insecticides commonly used in different agroecosystems (Goudegnon et al, 2000;Martin et al, 2006;Godonou et al, 2009;Agboyi et al, 2013). As a reaction to this phenomenon, cabbage producers have entered the vicious circle of increasing both insecticide dosage rates and spraying frequencies (Ahouangninou et al, 2012), which can lead to environmental and health hazards (Pimentel et al, 1997;Gallivan et al, 2001).…”
Section: Introductionmentioning
confidence: 91%
“…According to Gnago et al [5], caterpillars of the P. xylostella, seem to have developed a certain resistance against the insecticide Kart 500 SP. Odhiambo et al [6] noticed these forms of resistance to insecticides of pyrethrinoïd type and DDT (Dichloro-Diphenyl-Trichloro-ethane) too; these are abusively used at high dose by farmers [2]. The use of these chemical products gives rise to different varieties of resistant insects, which results in the emergence of different haplotypes between populations [7].…”
Section: Introductionmentioning
confidence: 99%